Novel targets for engineering Physostegia chlorotic mottle and tomato brown rugose fruit virus-resistant tomatoes: in silico prediction of tomato microRNA targets - Yahya Zakaria Abdou Gaafar; Heiko Ziebell (PeerJ, 2020)
Background Physostegia chlorotic mottle virus (PhCMoV; genus: Alphanucleorhabdovirus, family: Rhabdoviridae) and tomato brown rugose fruit virus (ToBRFV; genus: Tobamovirus, family: Virgaviridae) are newly emerging plant viruses that have a dramatic effect on tomato production. Among various known virus-control strategies, RNAi-mediated defence has shown the potential to protect plants against various pathogens including viral infections. Micro(mi)RNAs play a major role in RNAi-mediated defence. Methods Using in silico analyses, we investigated the possibility of tomato-encoded miRNAs (TomiRNA) to target PhCMoV and ToBRFV genomes using five different algorithms, i.e., miRanda, RNAhybrid, RNA22, Tapirhybrid and psRNATarget. Results The results revealed that 14 loci on PhCMoV and 10 loci on ToBRFV can be targeted by the TomiRNAs based on the prediction of at least three algorithms. Interestingly, one TomiRNA, miR6026, can target open reading frames from both viruses, i.e., the phosphoprotein encoding gene of PhCMoV, and the two replicase components of ToBRFV. There are currently no commercially available PhCMoV- or ToBRFV-resistant tomato varieties, therefore the predicted data provide useful information for the development of PhCMoV- and ToBFRV-resistant tomato plants.